The critical period of reservoir systems considering performance indices on Malaysia rivers - Saket Oskoui, Issa; Abdullah, Rozi; Montaseri, Majid (International Journal of Engineering and Technology, 2014)
The behavior of reservoir systems can be investigated using Critical Period (CP) which determines the aggregation level of the data (monthly or annual) that are required to be utilized in the reservoir analysis. Currently there are a number of methods that could approximate the behavior of reservoir systems, however the efficiency of these approaches have not been studied and verified for the Malaysia Rivers. In this study two different hypothetical reservoirs on Malaysia Rivers are selected. The stream flow data are subjected to preliminary analysis and evaluation of the fittest probability distribution function. Afterwards, the CP is estimated by applying a Monte Carlo simulation technique and considering performance indices. The CP from this study is used to determine the within-year or over-year behavior and these results are compared with those of the previous well-known equations in this area. It is observed that existing equations are incomplete and other parameters such as reliability and vulnerability should be considered to predict the behavior of reservoir systems. Consequently two separate regression equations are proposed to estimate the CP of these reservoir systems in Malaysia and some suggestions are made to generalize and extend this study. Keywords: Critical Period, Monte Carlo Simulation, Over-Year Behavior, Performance Indices, Reliability, Vulnerability, Within-Year Behavior.